 Are Neural Net architectures accidental discoveries?
 How much does it cost to build a private Ethereum blockchain network
 Which one is a better option  web3js or golang apis?
 Function 'sendTransaction'  can any error occur before the 'transactionHash' event?
 Contract Interaction
 Command line tool to interact with smart contract
 Listening for Deposits and Transaction Confirmations Web3js
 How to use Airdrop Contract Code
 Web3j Signature and Solidity Ecrecover
 Account created using web3 is not showing in geth console
 How to check used VideoCard's resources, if good or bad?
 Israeli Highway/Road Code
 Детский вопрос: кого бьет дальнобойщик?
 Hard Lump on Finger
 Can't create a new event template from an existing event template
 ACL and Drupal roles
 The use of Theis equation based on time
 I have an unidentified pressfit nut that I need to reproduce, can anyone tell me how to find this?
 Beta delta Agent  Consumption decision
 Aggregating in a Continuum
Identiy matrix with lambda
I need some help with my homework in a subject called "Matrices in statistics".
The task is to show that
$$ P_{ij}(\lambda)^{1} = P_{ij}\left(\frac{1}{\lambda}\right), $$ where $P_{ij} $ is an identity matrix, where the value of ith row and jth column is $\lambda.$
Here's my initial solution (which wasn't enough for the teacher):

We need to show, that $$ P_{ij}\left(\frac{1}{\lambda}\right) P_{ij}({\lambda}) =
P_{ij}({\lambda}) P_{ij}\left(\frac{1}{\lambda}\right) = I_n $$
So:
1) $$ P_{ij}\left(\frac{1}{\lambda}\right) P_{ij}({\lambda}) = P_{ij}\left(\frac{1}{\lambda} \cdot\lambda\right) = P_{ij}(1) = I_n$$
And
2) $$ P_{ij}({\lambda})P_{ij}\left(\frac{1}{\lambda}\right) = P_{ij}\left(\lambda\cdot\frac{1}{\lambda}\right) = P_{ij}(1) = I_n $$
Q.E.D
I submitted this solution, but my lecturer gave it back and wrote, that I need to supplement this solution. More precisely, I need to show, that
$$ \left(P_{ij}(\lambda)P_{ij}\left(\frac{1}{\lambda}

Our goal is to show that $P_{ij}(\lambda) P_{ij} (\dfrac{1}{\lambda}) = P_{ij} (\dfrac{1}{\lambda})P_{ij}(\lambda) = I_n$. To do this, we use the definition of matrix multiplication. That is, for $n \times n$ matrices $A$ and $B$, the product $AB$ of these matrices is the matrix $C$ with $ij$ element
$$
C_{ij} = \sum_{k = 1}^n A_{ik} B_{kj}
$$
If we let $A = P_{ij}(\lambda)$ and $B = P_{ij} (\dfrac{1}{\lambda})$ in this definition, we see that if $i \neq j$, then
$$
A_{ik} B_{kj} = 0
$$
for all $k$, since these matrices are zero everywhere except for on the diagonal. This tells us that the sum
$$
\sum_{k = 1}^n A_{ik} B_{kj}
$$
is equal to zero if $i \neq j$. That is, the product $AB = P_{ij}(\lambda) P_{ij} (\dfrac{1}{\lambda})$ is a matrix $C$ with $C_{ij} = 0$ for all $i \neq j$.
Now, if we have $i = j$, then we see that
$$
\sum_{k = 1}^n A_{ik} B_{kj} = 1
$$
since $A_{ik} B_{kj}$ is zero everywhere except when $k = i = j$. When $k = i = j$, then we have that $A_{ik}B_
20180312 21:40:36